Evaluation of design elements and the state of conservation of the unpaved road section in the state of pernambuco, brazil (Research, Society and Development, 2020)
The role played by highways in our country is of fundamental importance, considering that it is the main mode of transport of people and cargo. However, the brazilian road network is mostly in critical condition due to the lack of maintenance by the public sectors responsible. It is in this context that the interest emerges for the study of the stretch between the municipalities of Lagoa dos Gatos and Belém de Maria da PE-123, an unpaved state highway. This article aims to characterize the pathway, its pathologies, verify the design elements and present possible solutions to the identified problems. The data were obtained through topographic surveys, measurement of selected points, obtaining on-site images, satellite, and compared with official normative specifications. The evaluation of the stretch showed the total non-conformity of the track with the current technical requirements, evidencing the need for readjustment of the track, due to the poor conditions of the bearing strip, absence of drainage devices or any type of paving, improper cross-section and some pathological manifestations, such as holes, wheel trail and segregation of aggregates. In view of the table presented, the possible solutions to be implemented for the improvement of the tracing and its traffic condition are proposed. It can be appearing from the above in the study that the inefficiency of the agencies responsible in managing their infrastructure causes a greater financial detachment than would be necessary if regular maintenance works on the highway were carried out.